Enhancing the Impact of Implementation Strategies in Healthcare: A Research Agenda - Powell, Byron J.; Fernandez, Maria E.; Williams, Nathaniel J.; Aarons, Gregory A.; Beidas, Rinad S.; Lewis, Cara C.; McHugh, Sheena M.; Weiner, Bryan J. (Frontiers in Public Health, 2019)
The field of implementation science was developed to better understand the factors that facilitate or impede implementation and generate evidence for implementation strategies. In this article, we briefly review progress in implementation science, and suggest five priorities for enhancing the impact of implementation strategies. Specifically, we suggest the need to: (1) enhance methods for designing and tailoring implementation strategies; (2) specify and test mechanisms of change; (3) conduct more effectiveness research on discrete, multi-faceted, and tailored implementation strategies; (4) increase economic evaluations of implementation strategies; and (5) improve the tracking and reporting of implementation strategies. We believe that pursuing these priorities will advance implementation science by helping us to understand when, where, why, and how implementation strategies improve implementation effectiveness and subsequent health outcomes.